Towards a better understanding of foraging behavior to boost the expression of conditioned preferences for low-quality foods - Catanese, Francisco Hernan (2014)
Our objective was to explore the impact of feeding experiences with a low-quality food (LQF) on sheep foraging behavior when the availability of a high-quality food (HQF) is variable. Twenty-four female 2-y-old Merino sheep were randomly split into two groups; one group consumed oat straw (OS, a LQF) for 20 min and immediately after a ration of soybean meal (CS+), whereas the other group consumed OS but the offer of the meal was delayed 5 h (CS-; i.e., control). After conditioning, pairs of sheep from the same treatment were arranged and their dietary preferences were evaluated (15-min tests) in a u-shaped corridor where they faced a choice, at each end of the corridor, of OS (ad libitum) and HQF (alfalfa pellets [AP, first trial] or corn grain [CG, second trial] in one of six levels of availability: 2, 4, 8, 12, 24, or 32 g/animal). Data from each level of HQF availability was analyzed separately using a mixed-effects model. During both trials OS intake was almost negligible at high levels of HQF and similar between groups (Table 1). However, during high levels of restriction in HQF availability, OS intake increased abruptly (e.i., non-linear relationship) and we observed greater intakes for sheep in CS+ than sheep in CS- (Table 1). Increasing the quality of the HQF (APCG) reduced the likelihood of sheep accepting LQF at lower availabilities (e.g., at 8 g of HQF; P<0.034). In order to boost the benefits of a positive previous experience with LQF, restrictions should be placed on the accessibility and/or quality of the HQF (e.g., restricted foraging time, increased stock rate, etc.); otherwise, previous learning would remain silent or its effects over foraging behavior could be minimal.